The impact of non-linear viscoelastic property of blood in right coronary arteries hemodynamics — A numerical implementation. (July 2020) - Pinto, S.I.S.; Romano, E.; António, C.C.; Sousa, L.C.; Castro, C.F.
Abstract: The numerical implementation of the complex rheology of blood, namely the viscoelastic property, in hemodynamic simulations is still a challenge. A more accurate numerical tool is essential for diagnosis, prevention and treatment of atherosclerotic disease in arteries. In particular, in small vessels or vessels with stenosis and aneurysms, the elastic effects of blood should not be neglected. Since these are regions with high velocity gradients, the storage and release of elastic energy from red blood cells and the constant changes in shear rate have a demarked impact on the flow. Although the importance of the viscoelastic property is well emphasized in the literature, only a restrict set of authors have considered this property in their hemodynamic simulations. Thus, the aim of the present work is to go further and implement several viscoelastic models for blood in user-defined-functions of ANSYS software, in order to conclude which model is the most accurate for further applications. The Generalized Oldroyd-B (GOB) model, a quasi-linear model, and two non-linear models, the Multi-mode Giesekus and Simplified Phan-Thien/ Tanner (sPTT) models, were implemented. For right coronary arteries, velocity and wall shear stress were compared, considering a purely shear-thinning model, Carreau model, and the implemented viscoelastic models. An overall reduction of the velocity in regions of higher velocity gradients was observed, considering the non-linear viscoelastic multi-mode models (Giesekus and sPTT). Moreover, the difference in peak wall shear stress values considering these multi-mode viscoelastic models is close to half the magnitude (51%) of Carreau model solutions. Despite different arteries and hemodynamic conditions, the present results are in accordance with those found in the literature. The sPTT model should be the preferential option for further applications, since Giesekus model introduces the second normal stress difference, which so far has not been reported for blood. Highlights: Considering viscoelastic property of blood in hemodynamic simulations is a challenge. Several viscoelastic models for blood were implemented in UDFs of ANSYS software. Results using viscoelastic models are in accordance with those found in the literature. Peak WSS using the non-linear viscoelastic models are close to half considering Carreau. The non-linear viscoelastic sPTT model is preferential in hemodynamic applications.